Cultures and organizations : software of the mind: intercultural cooperation and its importance for survival - Hofstede, Geert , 1928-; Hofstede, Gert Jan; Minkov, Michael (New York : McGraw-Hill, 2010)
A study of how the place where we grew up shapes the way we think, feel, and act - with new dimensions and perspectives. Based on research conducted in more than seventy countries over a forty-year span, this title examines what drives people apart - when cooperation is so clearly in everyone's interest.
1. The rules of the social game -- 2. Studying cultural differences -- 3. More equal than others -- 4. I, we and they -- 5. He, She, and (S)he -- 6. What is different is dangerous -- 7. Yesterday, now, or later -- 8. Light or dark? -- 9. Pyramids, machines, markets, and families: organizing across nations -- 10. The elephant and the stork: organizational cultures -- 11. Intercultural encounters -- 12. The evolution of cultures
Includes bibliographical references and indexes
Keywords: Cultural pluralism; Ethnopsychology; Intercultural communication; International cooperation; National characteristics; Organization -- Research